Masseter Deoxygenation in Adults at Risk for Temporomandibular Disorders - Shah, N.; Melo, L.; Reid, W.D.; Cioffi, I. (Journal of dental research, 2019)
Patients with muscular temporomandibular disorder (TMD) present with abnormal oxygenation of the jaw muscles. Nonetheless, the deoxygenation pattern of jaw muscles of healthy subjects with frequent wake-time tooth-clenching episodes, who are at greater risk for TMD, has never been investigated. This case-control study compared the deoxygenation of the masseter during standardized tasks between TMD-free individuals with frequent self-reports of wake-time clenching and those with infrequent self-reports. University students (N = 255) filled out the Oral Behavior Checklist. Fourteen females with high versus low scores—high parafunctional (HP) group (n = 7, ≥80th percentile of score distribution) versus low parafunctional (LP) group (n = 7, ≤20th percentile)—completed 2 sessions during which they clenched at their maximum voluntary contraction (MVC) for 2 min and at 10% to 20% MVC for 20 min. Tissue oxygen saturation (StO2) and changes in oxygenated hemoglobin, deoxygenated hemoglobin, and total hemoglobin of the masseter were measured via near-infrared spectroscopy and analyzed with a generalized mixed effect model. A significant interaction effect (task × study group) was found on all outcome measures, indicating that the deoxygenation pattern of the HP group differed from the LP group (all P < 0.001). MVC of the masseter induced an almost 5-times-greater reduction of StO2 in the HP group as compared with the LP group (P = 0.023). However, the relative increase in StO2 at rest after the MVC was similar between groups (P > 0.05). At the end of the prolonged MVC task (10% to 20%), the blood flow (change in total hemoglobin) was almost 6 times higher in the LP group as compared with baseline. On the contrary, it increased minimally in the HP group (all P < 0.001). Healthy individuals at risk for TMD have abnormalities in masseter deoxygenation. Future prospective studies are needed to test whether this contributes to the onset of muscular TMD.